Mechanism and Selectivity of Cinchona Alkaloid Catalyzed [1,3]-Shifts of Allylic Trichloroacetimidates - Çelebi-Ölçüm, Nihan (2009)
Density Functional Theory calculations were used to investigate the [3,3]- and [1,3]-shifts of O-allylic trichloroacetimidates in the presence of cinchona alkaloids. Thermal [1,3]- and [3,3]-rearrangements proceed through concerted pseudopericyclic transition states to give the corresponding rearranged products. [1,3]-rearrangement is catalyzed via a double S(N)2' mechanism in which syn addition of the nucleophile is exclusively preferred in both steps. The catalyzed mechanism is favored by a 6.3 kcal/mol free energy difference compared to the alternative [3,3]-rearrangement pathway. The fast-reacting enantiomer is predicted to be determined by the availability of the H-bonding interaction between the catalyst and the substrate.